Testing Times: Introduction - Orero, Pilar; Hernández Falagán, David (Journal of Audiovisual Translation, 2021)
That COVID-19 touched all walks of life is an understatement. With the risk of sounding frivolous, compared with other impacts, COVID-19 had direct implications in research, and particularly in funded research activities with a strict schedule. Luckily, in the field of audiovisual translation we do not require any live samples or animals to be fed while in lockdown. Still, experimental programmed tests with people required alternative approaches. This special issue presents the social distancing challenges faced in user-centric research methodologies when human interaction is required.